Microsatellite characterisation and sex-typing in two invasive parakeet species, the monk parakeet Myiopsitta monachus and ring-necked parakeet Psittacula krameri - Francesca S. E. Dawson Pell; Ben J. Hatchwell; Alba Ortega-Segalerva; Deborah A. Dawson; Gavin J. Horsburgh; Juan Carlos Senar (Molecular Biology Reports, 2020)
Invasive species can have wide-ranging negative impacts, and an understanding of the process and success of invasions can be vital to determine management strategies, mitigate impacts and predict range expansions of such species. Monk parakeets ( Myiopsitta monachus ) and ring-necked parakeets ( Psittacula krameri ) are both widespread invasive species, but there has been little research into the genetic and social structure of these two species despite the potential links with invasion success. The aim of this study was to isolate novel microsatellite loci from the monk parakeet and characterise them in both monk and ring-necked parakeets in order to facilitate future investigations into their behaviour and population ecology. Sex-typing markers were also tested in both species. Of the 20 microsatellite loci assessed in 24 unrelated monk parakeets, 16 successfully amplified and were polymorphic displaying between 2 and 14 alleles (mean = 8.06). Expected heterozygosity ranged from 0.43 to 0.93 and observed heterozygosity ranged from 0.23 to 0.96. Nine of the 20 loci also successfully amplified and were polymorphic in the ring-necked parakeet, displaying between 2 and 10 alleles. Suitable markers to sex both species and a Z-linked microsatellite locus were identified. A multiplex marker set was validated for monk parakeets. These novel microsatellite loci will facilitate fine and broad-scale population genetic analyses of these two widespread invasive species.